2014
DOI: 10.1002/hfm.20547
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Truck Drivers’ Work Outside Their Cabs: Ergonomic Video Analyses Supplemented with National Accident Statistics

Abstract: Delivery truck drivers’ work contains various physically and psychosocially demanding work situations. Fifteen drivers’ and 8 other stakeholders’ identifications of such work situations were examined by video analyses in this study. The identifications were analyzed in‐depth by the researchers and compared with statistics on 3,507 accidents in the Finnish trucking industry. The aim was to determine what kind of identifications were made and to what degree the identifications coincided among the participants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…However, in the present study, we focus on a seldom-studied part of truck drivers’ work that is related to their tasks outside the cab. Several studies (see Chandler et al , 2017; Friswell and Williamson, 2010; Reiman et al , 2015; Shibuya et al , 2010; Wioland, 2013) have shown that the vast majority of these occupational accidents (referred to below simply as accidents) occur while performing tasks outside the cab.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study, we focus on a seldom-studied part of truck drivers’ work that is related to their tasks outside the cab. Several studies (see Chandler et al , 2017; Friswell and Williamson, 2010; Reiman et al , 2015; Shibuya et al , 2010; Wioland, 2013) have shown that the vast majority of these occupational accidents (referred to below simply as accidents) occur while performing tasks outside the cab.…”
Section: Introductionmentioning
confidence: 99%
“…Profits can be gained by standardized production to improve production efficiency for enterprises, while workers must continue working in designated work locations and standard time by engineers. In the actual production, a large number of upper limb tasks are performed by workers, which include some typical actions like grasping, lifting, lowering, carrying, pushing, pulling, and walking in the workshop, especially manual materials handling (MMH) [3][4][5][6]. MMH tasks are common in various industries such as manufacturing, agriculture, hospital, and construction.…”
Section: Introductionmentioning
confidence: 99%